2016
DOI: 10.1002/aenm.201601556
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Manganese Ions Trapping and Hydrofluoric Acid Scavenging Separator for Lithium Ion Batteries Based on Poly(ethylene‐alternate‐maleic acid) Dilithium Salt

Abstract: of the PF 6 − anion and solvent molecules, and lithium consumption, all of which adversely affect the solid electrolyte interphase (SEI) that passivates the negative electrode in a LIB and increase the cell impedance. [1] Simultaneously, the irreversible loss of Mn disrupts the structural integrity of the active material in the positive electrode. As a consequence, the cell experiences performance degradation and a reduced useful life. It is well documented that the Mn dissolution rate increases drastically at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 22 publications
2
57
0
Order By: Relevance
“…61,62 Galvanostatic cycling data for cells containing inhouse fabricated separators functionalized with poly-BPA, poly-PEI, and Na 4 EDTA and 1 M LiPF 6 /EC:DMC (1:1 v/v) recorded at 55…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…61,62 Galvanostatic cycling data for cells containing inhouse fabricated separators functionalized with poly-BPA, poly-PEI, and Na 4 EDTA and 1 M LiPF 6 /EC:DMC (1:1 v/v) recorded at 55…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that Mn trapping and the associated benefits for capacity retention in LMO-graphite cells upon high-temperature cycling can be obtained with several inexpensive commercially available polymeric or molecular ion-trapping materials. [61][62][63] Furthermore, we have also demonstrated that besides trapping Mn ions, these materials can scavenge acidic species (HF, POF 3 , etc.) and also act as a source of sacrificial Li + or Na + ions.…”
Section: A6316mentioning
confidence: 99%
See 3 more Smart Citations